Ocena efektywności przedsięwzięć outsourcingowych z zakresu systemów informatycznych - Sobińska, Małgorzata (Effectiveness Assessment of Outsourcing Information Systems, 2005)
The test of the capital ventures efficiency is a condition of a rational working of an organization. In the article there are characterized the methods of analyzing outsourcing ventures efficiency. Information systems outsourcing is taken into special consideration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 405-412